Unethical and unlogical methods in culture of productive logic and modern intellectuality (Journal of Philosophy Culture and Political Science, 2018)
The article deals with topical issues and unethical practices in the culture of non-logical logic productive at present and especially the formation of the intellectual nation. Abstract makes a critical analysis of the content of speculative, sophistical and others. Methods that juggles with words and meaning are konkertnye and business advice in dealing with them. And in this article offers specific methodology and guidelines, which can become an auxiliary lever in the fight against speculative tricks in the process of thinking and expressing their own views. In a few paragraphs provide specific recommendations of sound and certain steps in the building of productive thinking facilitates timely finds flaws his and others’ opinions. These thoughts are expressed specifically in the following paragraphs: too much fascination with terminology; slovovyrazheny complications; speculative expression of thought, ie,sophistry uhuschrenie thoughts that leads to psevdointellektualnoy game; and proposes, subject to certain ethics of dialogue and thinking entity armed productive logic; productive logics should not vozvelechit themselves in relationships with others. These and other design offers unobtrusive ways, as it were recommendations for consideration.Key words: productive logic, intellectualism, methodology, culture of thinking is unethical, sophistry, speculation, youth, philosophy.